Analisis Supplier Relationship Management (SRM) Produk Bahan Cat pada PT. XYZ Menggunakan Analytical Hierarchy Process (AHP) - Diansyah, Muhamad Renal; Sari, Rini Mulyani (Universitas Batanghari, 2024)
PT. XYZ, a major automotive company in Indonesia, requires supplier evaluation to maintain the stability of its production processes. To achieve this, a comprehensive analysis is necessary, utilizing the Analytic Hierarchy Process (AHP) method. This method involves evaluating criteria such as delivery time, price, and quality. The number of suppliers evaluated is two. Data for the criteria was gathered through direct interviews with the Purchasing Administration Division. The results of the AHP analysis indicate that Supplier A is the best supplier for providing raw materials to PT. XYZ.